The Poetics of Islamic Legitimacy - Michelle Hartman (International Institute of Islamic Thought, 2004)
In The Poetics of Islamic Legitimacy, Suzanne Pinckney Stetkevych effectively debunks the myth that the classical Arabic panegyric ode (qasidat al-madh) is merely a descriptive, prescriptive, or sycophantic poetic genre by demonstrating its dynamic engagements with what she terms “Arabo-Islamic court life.” The book builds on her previous work (e.g., The Mute Immortals Speak [Cornell University Press: 1993]), using an approach that blends an understanding of myth, rite, and archetype in the classical Arabic qasidah with historically grounded, contextualized interpretations of these poems. Her insightful, close readings of individual poems are coupled with a detailed exploration of the classical Arabic qasidah’s social and ritual functions – from the pre-Islamic period, through its early days, and continuing through the Umayyad and `Abbasid periods. This book’s specific argument is that the panegyric ode “created, encoded, and promulgated a myth and ideology of legitimate Arabo- Islamic rule” (p. ix). She uses a range of contemporary sources, including anecdotal material about poetry and poets, in her interpretations. This grounds her detailed and specific literary analyses in a broader sociopolitical, historical, and cultural setting and invigorates her arguments about poetry’s role in relation to power and leadership. Each chapter treats one aspect of this overall argument and progresses chronologically, beginning with pre-Islamic Arabia and ending with Andalusia. Each chapter is highly structured and begins by setting a context. Stetkevych then explicates the paradigms and theories employed (e.g., Van Gennep’s rite of passage and Mauss’ formulation of ritual exchange), before providing a translation of the poem(s) to be analyzed. Finally, she analyzes one or more poems, reading each section meticulously in relation to the previously outlined contexts, paradigms, and theories, as well as the Arabic literary tradition. She also notes grammatical and linguistic points and the sociopolitical, historical and/or cultural elements affecting its composition. She concludes by linking each chapter to the larger idea that binds the book together – how the poems shore up or undermine the legitimacy of Arabo-Islamic leaders ...